Application Research on "the Evaluated Lowest Bid Price Method" in Bidding. Issue 5 (March 2019) - Zhang, Junling
Abstract: This paper analyzes and discusses the "winning the bid at a low price" and the "the evaluated lowest bid price method" which have been widely concerned and discussed in recent years. Through the analysis of "the evaluated lowest bid price method", it is concluded that "the evaluated lowest bid price method" is not equal to "the lowest bid price method", nor is it the essential reason for the phenomenon of "winning the bid at a low price". It further points out the problems existing in the application of "the evaluated lowest bid price method" in bidding practice, and puts forward corresponding countermeasures and suggestions.